A first-in-human phase 1 dose escalation study of spartalizumab (PDR001), an anti–PD-1 antibody, in patients with advanced solid tumors. Issue 1 (15th March 2020) - Naing, Aung; Gainor, Justin F; Gelderblom, Hans; Forde, Patrick M; Butler, Marcus O; Lin, Chia-Chi; Sharma, Sunil; Ochoa de Olza, Maria; Varga, Andrea; Taylor, Matthew; Schellens, Jan H M; Wu, Hongqian; et al.
Abstract : Background: Spartalizumab is a humanized IgG4κ monoclonal antibody that binds programmed death-1 (PD-1) and blocks its interaction with PD-L1 and PD-L2. This phase 1/2 study was designed to assess the safety, pharmacokinetics, and preliminary efficacy of spartalizumab in patients with advanced or metastatic solid tumors. Methods: In the phase 1 part of the study, 58 patients received spartalizumab, intravenously, at doses of 1, 3, or 10 mg/kg, administered every 2 weeks (Q2W), or 3 or 5 mg/kg every 4 weeks (Q4W). Results: Patients had a wide range of tumor types, most commonly sarcoma (28%) and metastatic renal cell carcinoma (10%); other tumor types were reported in ≤3 patients each. Most patients (93%) had received prior antineoplastic therapy (median three prior lines) and two-thirds of the population had tumor biopsies negative for PD-L1 expression at baseline. The maximum tolerated dose was not reached. The recommended phase 2 doses were selected as 400 mg Q4W or 300 mg Q3W. No dose-limiting toxicities were observed, and adverse events included those typical of other PD-1 antibodies. The most common treatment-related adverse events of any grade were fatigue (22%), diarrhea (17%), pruritus (14%), hypothyroidism (10%), and nausea (10%). Partial responses occurred in two patients (response rate 3.4%); one with atypical carcinoid tumor of the lung and one with anal cancer. Paired tumor biopsies from patients taken at baseline and on treatment suggested an on-treatment increase in CD8+ lymphocyte infiltration in patients with clinical benefit. Conclusions: Spartalizumab was well tolerated at all doses tested in patients with previously treated advanced solid tumors. On-treatment immune activation was seen in tumor biopsies; however, limited clinical activity was reported in this heavily pretreated, heterogeneous population. The phase 2 part of this study is ongoing in select tumor types. Trial registration number: NCT02404441 .